SYNTHESIS AND POLYMERIZATION OF T-BOC PROTECTED MALEIMIDE MONOMERS - N-(T-BUTYLOXYCARBONYLOXY) MALEIMIDE AND N-[P-(T-BUTYLOXYCARBONYLOXY) PHENYL]-MALEIMIDE - AHN, KD; KOO, DI; WILLSON, CG (BUTTERWORTH-HEINEMANN LTD, 1995)
Two t-butyloxycarbonyl (t-BOC) protected maleimide monomers, N-(t-butyloxycarbonyloxy)maleimide (t-BOCOMI) and N-[p-(t-butyloxycarbonyloxy)phenyl]maleimide (t-BOCOPMI), have been synthesized and polymerized. The t-BOC group was used to protect the hydroxy groups of the starting N-substituted maleimides, N-hydroxymaleimide (HOMI) and N-(p-hydroxyphenyl)maleimide (HOPMI). t-BOCOMI and t-BOCOPMI were copolymerized with styrene derivatives (X-St) to obtain the t-BOC protected polymers P(t-BOCOMI/X-St) and P(t-BOCOPMI/X-St) in high conversions. P(t-BOCOMI/St) and P(t-BOCOPMI/St) were cleanly deprotected by heating the polymers to 110 and 175 degrees C, respectively. The deprotection temperature of the copolymers of t-BOCOMI (ca. 100 degrees C) is the lowest among the known t-BOC protected polymers. Deprotection of P(t-BOCOMI/X-St) and P(t-BOCOPMI/X-St) produced the corresponding polymers having HOMI and HOPMI structures, respectively, and resulted in large changes in physical properties. The deprotected polymers have very high glass transition temperatures (above 250 degrees C) and good solubility in aqueous base solutions, whereas the t-BOC polymers are only soluble in organic solvents. P(t-BOCOMI/St) was found to have desirably low ultra-violet absorption and high sensitivity in resist formulations.
Keywords: COPOLYMERS; RESINS